Mesenchymal Stem Cell Combination Therapy Via Intravenous and C-Arm– Guided Spinal Delivery: A Systematic Review and Meta-Analytic Framework For Neurological and Functional Recovery - Deby Susanti Pada Vinski Vinski; Natasha Cinta Vinski; Sunaryo Kusumo; Carles Siagian (Riviera Publishing, 2026)
Mesenchymal stem/stromal cells (MSCs) have emerged as a promising therapeutic platform for neurological and spinal disorders due to their immunomodulatory, trophic, anti-inflammatory, and regenerative properties. Clinical studies have evaluated MSCs via intravenous (IV) and intrathecal (IT) or intraspinal routes, yet the translational rationale for combining systemic and targeted spinal delivery remains insufficiently synthesized. C-arm-guided spinal administration may enhance procedural precision, optimize cerebrospinal or peri-spinal targeting, and potentially improve regional bioavailability. This review aimed to examine the clinical rationale, safety profile, and therapeutic potential of combined MSC administration through IV and C-arm-guided spinal routes, focusing on neurological recovery, pain, functional independence, and spinal health-related performance. The study was structured as a PRISMA 2020-aligned systematic review with a meta-analytic framework. Evidence was synthesized from comparative clinical literature on MSC therapy in spinal cord injury, stroke sequelae, multiple sclerosis, amyotrophic lateral sclerosis, and related disorders. Risk of bias was assessed using RoB 2 and ROBINS-I. A route-specific quantitative safety meta-analysis was performed using extractable data on treatment-related serious adverse events. From 2,308 identified records, 9 studies were included in the qualitative synthesis and 6 primary studies in the safety meta-analysis. Evidence indicates that IT delivery is feasible and generally safe, with no consistent signal of serious procedure-related toxicity. In spinal cord injury, IT MSC delivery demonstrated encouraging neurological improvement signals. IV delivery offers broader systemic immunomodulation. In the pooled safety analysis, treatment-related serious adverse events were rare, with estimates approaching zero and no detectable heterogeneity.